DISTINCTION AND DIFFERENCE: REVISITING THE QUESTION OF TASTE - Rebentisch, Juliane (The Nordic Journal of Aesthetics, 2018)
The essay discusses the logic of distinction under the sign of the contemporary culture of difference and proposes a discussion of the relationship between taste and contemporary art. The recent trend toward greater individualization might have rendered social codes more permeable. But this state of affairs is neither the opposite of the standardization nor does it imply that the social logic of distinction has been suspended. It has merely undergone further differentiation, but without abolishing the signifiers of status. On the one hand art as a commodity partakes in the respective developments, on the other, certain strands in contemporary art can also be read as opposing the subject of aesthetic experience to the subject of consumerist taste.